2019
DOI: 10.1177/1039856219848835
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief intervention aimed at increasing distress tolerance for individuals in crisis or at risk of self-harm

Abstract: Objective: This study evaluated a brief psychological intervention aimed at improving distress tolerance and decreasing future admissions for individuals presenting to a mental health service in the context of crisis or self-harm. Methods: Eighty-five participants completed The Crisis Intervention Package at the point of contact with the mental health service. The outcome of the intervention was evaluated through pre- and post-scores on the Distress Tolerance Scale and future hospital admissions. Results: Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…As noted in prior studies of crisis message content [19,20], depending on perceived levels of crisis predictability and controllability, recipients of media messages are prone to emotions such as anger, fear, and sadness in addition to ambient levels of anxiety already being experienced due to the crisis itself [21]. An alternative approach would be to promote distress tolerance and emotional resilience rather than inflate fear, anger, or other negative states [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in prior studies of crisis message content [19,20], depending on perceived levels of crisis predictability and controllability, recipients of media messages are prone to emotions such as anger, fear, and sadness in addition to ambient levels of anxiety already being experienced due to the crisis itself [21]. An alternative approach would be to promote distress tolerance and emotional resilience rather than inflate fear, anger, or other negative states [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…As distress intolerance is not unique to EUPD, aspects of this skills training have been adapted to other mental health conditions. A brief mental health crisis intervention package demonstrated effectiveness at increasing DT and self-management skills (Yardley et al, 2019). Distress tolerance interventions have also been developed aimed at improving self-management of chronic physical health conditions, but it has been reported that further research into the efficacy of these is needed (Russell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the skills included in the CTB were acceptable to those presenting in crisis. This is not too surprising as CTB skills were derived from psychological approaches, including dialectical, cognitive, and behavioural therapies that have demonstrable efficacy for those at risk of self-harm and/or experiencing suicidal thoughts (Yardley et al, 2019 ; McCabe et al, 2018 ). However, the current findings also validate the acceptability and value of skills-based interventions delivered via telephone for this client group (Bidargaddi et al, 2015 ; Mulligan et al, 2014 ; Rushton et al, 2019 ; Irvine et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%